Electroanatomy of hippocampal activity patterns: theta, gamma waves, sharp wave-ripples, and dentate spikes - Paleologos, Nicholas; Vöröslakos, Mihály; Gonzalez, Joaquin; Maslarova, Anna; Aykan, Deren; Liu, Anli A.; Buzsáki, György (Frontiers in Behavioral Neuroscience, 2025)
Monitoring representative fractions of neurons from multiple brain circuits in behaving animals is necessary for understanding how different brain regions interact. Using multishank, high-density recording silicon probes (up to 1,024 sites), we describe the main characteristic LFP patterns in the hippocampus, including sharp wave-ripples (SPW-Rs), dentate spikes (DSs), theta, and gamma oscillations. Our novel observations primarily relate to the distinction between subclasses of SPW-Rs and DSs, as well as their neuronal spiking correlations. In addition to the classical SPW-Rs, initiated in the CA2-3 recurrent collateral system and characterized by a large negative sharp wave (sink) in the mid-CA1 stratum radiatum (SPW-RRad), a small subset of ripples, associated with a sink in CA1 str. lacunosum-moleculare was also observed (SPW-RLM). The two types of ripple events differed in frequency, magnitude, and neuronal correlates. CA3 pyramidal neurons were strongly active during SPW-RRad but not during (SPW-RLM). DSs could also be grouped further based on their excitatory inputs from the medial and lateral entorhinal cortex (DSMEC and DSLEC), by their impact on their physiological targets, and by the brain states into which they were embedded. Overall, our experiments demonstrate the utility and need for high-density recording of both LFP and spiking activity for the appropriate classification of seemingly similar events. These distinctions relate not only to their neurogenesis but also to their behavioral-cognitive contributions.